A Contrastive Investigation into Linguistic Feature of Socio-Cultural Propaganda Slogans in English and Vietnamese - Trương Thành Khải (2011)
This study reports a contrastive investigation into linguistic features of socio-cultural propaganda slogans in English and Vietnamese. An analysis is made to find out how types of sentences, types …